Efficacy of Next-Generation Sequencing in Identifying Genetic Markers for Prostate Cancer Risk - Fahad H. Alaithan; Raghad H. Alaithan; Tauheed Ahmed (Journal of Pharmacy and Bioallied Sciences)
Background: Prostate cancer is one of the most prevalent cancers among men worldwide. The identification of genetic markers that contribute to the risk of prostate cancer can significantly enhance early diagnosis and personalized treatment strategies. Next-Generation Sequencing (NGS) has emerged as a powerful tool for uncovering genetic variations associated with various cancers, including prostate cancer. Materials and Methods: A cohort of 200 men, consisting 100 diagnosed with prostate cancer and 100 healthy controls, was recruited for this study. DNA samples were extracted from blood and tumor tissues, followed by library preparation and sequencing using an Illumina platform. Bioinformatic analysis was conducted to identify single nucleotide polymorphisms (SNPs), copy number variations (CNVs), and other genetic alterations linked to prostate cancer. Statistical analysis was performed to assess the association between identified genetic markers and prostate cancer risk. Results: NGS identified a total of 450 genetic variants, with 50 SNPs showing a strong association with prostate cancer risk (P < 0.001). Notably, the BRCA1, BRCA2, and HOXB13 genes exhibited significant variants in 20% of the prostate cancer patients. Furthermore, CNVs in the MYC and PTEN genes were observed in 15% and 10% of the patients, respectively. The control group displayed a significantly lower frequency of these genetic alterations, reinforcing their potential role as risk markers for prostate cancer. Conclusion: This study demonstrates the efficacy of NGS in identifying genetic markers associated with prostate cancer risk.